Special Service Management Analysis at Aisyiyah Bustanul Athfal Batusangkar Kindergarten - Ramadhanty, Dwifa; Yaswinda, Yaswinda; Suryana, Dadan; Mayar, Farida (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
This article discusses the implementation of various special services at TK Aisyiyah Bustanul Athfal Batusangkar, highlighting the importance of managing these services effectively. The aim of the study was to analyze the planning, implementation, and control of these special services. The research is field-based, using qualitative descriptive methods, which focus on describing the phenomena observed through narratives or descriptions as outlined by Sugiyono. Primary data was sourced from the Principal of Aisyiyah Bustanul Athfal Batusangkar Kindergarten, while secondary data came from teachers and parents of the students. Data collection techniques involved observation and interviews, with qualitative analysis following the stages of data reduction, presentation, and conclusion. The study found that: (1) the planned services included Qur'an tutoring using the Iqra' and fluttering methods, memorization of hadith, selected prayers, and Juz 30 of the Qur'an, as well as activities like singing, dancing, painting, drawing, marching band, little doctor and little police training, parenting, and field trips. (2) The services were implemented according to the plan, with individual, group, and classical programs. The main challenge was the incomplete implementation of services in the second semester due to the Covid-19 pandemic, which required children to study from home. (3) The control of special services was effective, with the principal overseeing and evaluating all activities for their effectiveness.